Luiz Ruffato e o romance proletário no Brasil - Maria Isabel da Silveira Bordini (2019)
The main purpose of this work is to compare the political and aesthetic literary project by the contemporary Brazilian writer, Luiz Ruffato, specially the pentalogy called Inferno Provisório, with the brasilian tradition of the proletarian novel, which started in Brazil in the 30's. I also intend to compare Luiz Ruffato's work with the development of this so called brasilian tradition of the proletarian novel, as it evolves during the following decades. Some more specific purposes of this work are: 1) toanalyse the proletarian novels published in Brazil in the 30's and search some common elements that allow us to define what a proletarian novel is; 2) to identify a line of continuity and evolution of Brazilian proletarian novel in the following decades, by mapping the novels that address this subject; 3) to analyse the sociological and cultural grounds of the formation of Brazilian working class, in order to research if and how this process influences the development of a literature concerned with this subject; 4) to investigate the political and aesthetic literary projectby Luiz Ruffato, adressing the conjunction of its aesthetic elements and its purpose of review and supplementation of Brazilian literary canon; 5) to adress the matter of engaged intellectual - as an issue that Brazilian novelists in the 30's needed to face and formally respond - and to analyse how it is presented in Inferno Provisório, by Ruffato.